Construcción de estándares para métodos de trabajo de los procesos de producción de las pymes del sector de la construcción de la ciudad de Bogotá D.C. (2021)
The standardization of the method used by the process of the construction industry showing a low investigation, emphasized to the technical, materials or tools used, issued a decrease in the industry growing, in the same way leaving a bad image to the development of the industry. It decides to development an investigation in to find the critical factors that lead to economics lose for the PyMesin Bogota city, skewing the information to the construction sector in order to establish the job positions of a specific phase, leaving as result the positions job that requires standards to improve the development of the activities of the process.